Arsenic and Boron Levels in Irrigation Water, Soil, and Green Leafy Vegetables. Issue 2 (4th March 2018) - Ghasemidehkordi, Bahareh; Malekirad, Ali Akbar; Nazem, Habibollah; Fazilati, Mohammad; Salavati, Hossein; Rezaei, Mohammad
ABSTRACT: Vegetable production sometimes takes place in close proximity to heavy industry. It is necessary to determine whether vegetables grown under these conditions contain high levels of pollutants. The semimetals arsenic (As) and boron (B) are toxic in high concentration. Levels of As and B were determined in irrigation water, soil, and the green leafy vegetables Leek ( Allium ampeloprasum L), Wakegi Onion ( A. wakegi L), Tarragon ( Artemisia dracunculus L), Coriander ( Coriandrum sativum L), Garden Cress ( Lepidium sativum L), Mint ( Mentha arvensis L), Parsley ( Petroselinum crispum Nyman Consp), Radish ( Raphanus sativus L), Spinach ( Spinacia oleracea L), and Fenugreek ( Trigonella foenum-graecum L) using inductively coupled plasma–optical emission spectroscopy. Samples were obtained from agricultural sites in Markazi Province, Iran. Leek contained 174.32 ± 273.33 µg·kg −1 of As and fenugreek contained 12029.99 ± 18312.6 µg·kg −1 dry weight of B, indicating that they are high accumulators. Plants can accumulate semimetals from water and soil. In irrigation water, the As content was 24.96 ± 0.18 µg·kg −1 and B content was 13, 627.002 ± 10, 401.8 µg·kg −1 ; in soil, the As content was 2402.72 ± 1103.38 µg·kg −1 and B content was 19, 189.13 ± 4528.09 µg·kg −1, respectively. The contents of As but not B in the vegetables exceeded safe standards, indicating that production in contaminated soil can cause them to be unsafe for human consumption.